Aedes mosquitoes and Aedes-borne arboviruses in Africa - Weetman, David (2021)
The Zika crisis drew attention to the long-overlooked problem of arboviruses transmitted by Aedes mosquitoes in Africa. Yellow fever, dengue, chikungunya and Zika are poorly controlled in Africa and often go unrecognized. However, to combat these diseases, both in Africa and worldwide, it is crucial that this situation changes. Here, we review available data on the distribution of each disease in Africa, their Aedes vectors, transmission potential, and challenges and opportunities for Aedes control. Data on disease and vector ranges are sparse, and consequently maps of risk are uncertain. Issues such as genetic and ecological diversity, and opportunities for integration with malaria control, are primarily African; others such as ever-increasing urbanization, insecticide resistance and lack of evidence for most control-interventions reflect problems throughout the tropics. We identify key knowledge gaps and future research areas, and in particular, highlight the need to improve knowledge of the distributions of disease and major vectors, insecticide resistance, and to develop specific plans and capacity for arboviral disease surveillance, prevention and outbreak responses.